ANALYSIS OF LANGUAGE STYLE IN INDONESIAN LANGUAGE MEMES: A REFLECTION OF POP CULTURE IN GENERATION Z: ANALISIS GAYA BAHASA DALAM MEME BERBAHASA INDONESIA: REFLEKSI BUDAYA POP PADA GENERASI Z - Ahmad Sulthoni; Sasi Wirta Ayu; Elinda Dwi Arifah; Kartika Apriliani Silaban (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Memes, as part of the digital cultural landscape, have evolved into a widely used means of communication among Generation Z. More than just humorous content, memes often carry embedded messages involving social critique, cultural expressions, and political undertones. This study aims to examine the linguistic styles employed in Indonesian-language memes and how these styles illustrate aspects of pop culture within Generation Z. A descriptive qualitative approach was applied using stylistic and semiotic analysis. The data were drawn from popular memes circulating on social media platforms such as Instagram and Twitter. The findings indicate that the most common language styles used include irony, metaphor, hyperbole, and sarcasm, frequently accompanied by slang and code-mixing. These stylistic patterns reflect Generation Z‘s expressive, critical, and highly connected nature within global pop culture. Memes thus serve as tools for cultural articulation and social commentary among young Indonesians.